Rural-urban disparity in cancer burden and care: findings from an Indian cancer registry - Divya Khanna; Priyanka Sharma; Atul Budukh; Rajesh Vishwakarma; Anand N. Sharma; Sonali Bagal; Varsha Tripathi; Vijay Kumar Maurya; Pankaj Chaturvedi; Satyajit Pradhan (BMC Cancer, 2024)
Abstract Background Cancer incidence and mortality vary across the globe, with nearly two-thirds of cancer-related deaths occurring in low- and middle-income countries. The rural-urban disparity in socio-demographic, behavioural, and lifestyle-related factors, as well as in access to cancer care, is one of the contributing factors. Population-based cancer registries serve as a measure for understanding the burden of cancer. We aimed to evaluate the rural-urban disparity in cancer burden and care of patients registered by an Indian population-based cancer registry. Methods This study collected data from Varanasi, Uttar Pradesh, India, between 2017 and 2019. Sex and site-specific age-standardised rates for incidence and mortality per 100,000 population were calculated. Rural-urban disparities in cancer incidence and mortality were estimated through rate differences and standardised rate ratios (with 95% confidence intervals). Univariable and multivariable regressions were applied to determine any significant differences in socio-demographic and cancer-related variables according to place of residence (rural/urban). Crude and adjusted odds ratios with 95% confidence intervals were calculated. Results 6721 cancer patients were registered during the study duration. Urban patients were older and had better literacy and socioeconomic levels, while rural patients had higher odds of having unskilled or semi-skilled professions. Diagnostic and clinical confirmation for cancer was significantly higher in urban patients, while verbal autopsy-based confirmation was higher in rural patients. Rural patients were more likely to receive palliative or alternative systems of medicine, and urban patients had higher chances of treatment completion. Significantly higher incidence and mortality were observed for oral cancer among urban men and for cervical cancer among rural women. Despite the higher incidence of breast cancer in urban women, significantly higher mortality was observed in rural women. Conclusions Low- and middle-income countries are facing dual challenges for cancer control and prevention. Their urban populations experience unhealthy lifestyles, while their rural populations lack healthcare accessibility. The distinctness in cancer burden and pattern calls for a re-evaluation of cancer control strategies that are tailor-made with an understanding of urban-rural disparities. Context-specific interventional programmes targeting risk-factor modifications, cancer awareness, early detection, and accessibility to diagnosis and care are essential.